1999
DOI: 10.1074/jbc.274.31.21528
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Akt3 in Estrogen Receptor-deficient Breast Cancers and Androgen-independent Prostate Cancer Lines

Abstract: We measured the insulin-stimulated amount of Akt1, Akt2, and Akt3 enzymatic activities in four breast cancer cell lines and three prostate cancer cell lines. In the estrogen receptor-deficient breast cancer cells and the androgen-insensitive prostate cells, the amount of Akt3 enzymatic activity was approximately 20 -60-fold higher than in the cells that were estrogen-or androgen-responsive. In contrast, the levels of Akt1 and -2 were not increased in these cells. The increase in Akt3 enzyme activity correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
305
1
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(321 citation statements)
references
References 29 publications
(42 reference statements)
9
305
1
6
Order By: Relevance
“…1A). In the control experiments, all three Akt isoforms were detected in MDA-MB-231 cells, human breast cancer cells, consistent with previous reports [14]. When THP-1 cells were co-cultured with MCF-7, a representative breast cancer cell line, Western blotting analysis revealed an increase in Akt phosphorylation at both 308 and 473 residues, suggesting that breast cancer cells can stimulate Akt activation in macrophage (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1A). In the control experiments, all three Akt isoforms were detected in MDA-MB-231 cells, human breast cancer cells, consistent with previous reports [14]. When THP-1 cells were co-cultured with MCF-7, a representative breast cancer cell line, Western blotting analysis revealed an increase in Akt phosphorylation at both 308 and 473 residues, suggesting that breast cancer cells can stimulate Akt activation in macrophage (Fig.…”
Section: Resultssupporting
confidence: 90%
“…while Akt3 shows a more restricted expression pattern [14]. Both genetic and molecular studies revealed that Akt isozymes are regulated by PI3 Kinases/PDK1 or mTOR [15].…”
mentioning
confidence: 99%
“…Akt gene amplification has been observed in prostate cancer 78,79 and other malignancies including ovarian cancer, 80,81 pancreatic cancer, 82 gastric cancer, 83 thyroid cancer, 84 and breast cancer. 80,85 Elevated Akt expression and kinase activities are associated with a hormone-resistant phenotype and correlates with a poor prognosis in human prostate cancer and breast cancer.…”
Section: Genetic Perturbation and Dysregulation Of The Pi3-k-akt Pathwaymentioning
confidence: 99%
“…80,85 Elevated Akt expression and kinase activities are associated with a hormone-resistant phenotype and correlates with a poor prognosis in human prostate cancer and breast cancer. 78,79,85,86 Upstream of Akt, amplification of PI3-K has been reported for prostate, 79 ovarian, 87,88 colon, 88 and breast cancer. 85 Several protein-tyrosine kinases (PTKs), which act upstream of the PI3-K and are important regulators of the PI3-K-Akt pathway, have been found overexpressed in various cancers because of activating mutations or other genetic alterations.…”
Section: Genetic Perturbation and Dysregulation Of The Pi3-k-akt Pathwaymentioning
confidence: 99%
“…The AKT 3 primers were: forward primer 5 0 -ATGAGCGATGT TACCATTGT-3 0 (corresponding to position 1 -20, GenBank accession number NM_005465) and reverse primer 5 0 -CAGTCTGTCTGCTACAGCCTGGATA-3 0 (corresponding to positions 327 -303) (Nakatani et al, 1999). PCR program for all AKT isoforms was 30 cycles of 941C for 45 s, 551C for 45 s and 721C for 45 s.…”
Section: Telomeric Repeat Amplification Protocol Assaymentioning
confidence: 99%